2003
DOI: 10.1523/jneurosci.23-10-04092.2003
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis and Vesicle Recycling at a Ribbon Synapse

Abstract: At ribbon synapses, where exocytosis is regulated by graded depolarization, vesicles can fuse very rapidly with the plasma membrane (complete discharge of the releasable pool in approximately 200 msec). Vesicles are also retrieved very rapidly (time constant of approximately 1 sec), leading us to wonder whether their retrieval uses an unusual mechanism. To study this, we exposed isolated bipolar neurons from goldfish retina to cationized ferritin. This electron-dense marker uniformly decorated the cell membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
145
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(160 citation statements)
references
References 30 publications
(39 reference statements)
13
145
0
2
Order By: Relevance
“…Indeed, both evagination with increasing stimulation intensity and the placement of the next vesicle at the crest have been reported in lateral line ribbon synapses (Fields and Ellisman, 1985). Moreover, the relatively large, tubular endocytic figures observed after strong depolarization could represent the retrieval of several vesicles' worth of membrane (Paillart et al, 2003;Royle and Lagnado, 2003), such as might occur from retrieving several vesicles following compound fusion (although other interpretations are possible). Alternatively, but not exclusively, the global calcium stimulus provided by calcium uncaging might trigger the fusion of numerous vesicles outside the active zone.…”
Section: Fusion Scenarios and Ribbon Functionmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, both evagination with increasing stimulation intensity and the placement of the next vesicle at the crest have been reported in lateral line ribbon synapses (Fields and Ellisman, 1985). Moreover, the relatively large, tubular endocytic figures observed after strong depolarization could represent the retrieval of several vesicles' worth of membrane (Paillart et al, 2003;Royle and Lagnado, 2003), such as might occur from retrieving several vesicles following compound fusion (although other interpretations are possible). Alternatively, but not exclusively, the global calcium stimulus provided by calcium uncaging might trigger the fusion of numerous vesicles outside the active zone.…”
Section: Fusion Scenarios and Ribbon Functionmentioning
confidence: 94%
“…The significance of these species differences is unclear because, on the one hand, the immunolabeling studies in nonmammalian vertebrates were performed using antibodies to mammalian isoforms and, on the other hand, little is known about the calcium dependence of release at mammalian retinal ribbon synapses. A straightforward interpretation of isoform expression and the calcium sensitivity of release may be further complicated by the putative role of synaptotagmin in endocytosis and the different modes of endocytosis that a cell may preferentially utilize (Llinas et al, 2004;Holt et al, 2003;Paillart et al, 2003).…”
Section: Fusion Machinerymentioning
confidence: 99%
“…In this way, functional vesicle pools that were previously labelled with FM-dye can be directly identified in electron micrographs. This approach has been used extensively and highly successfully in cultured neurons 7,10,24,28,30,[32][33][34] , a number of large, peripheral terminals [26][27][28][29]31,[35][36][37] , and large central release sites such as calyx of Held 25 revealing important information about organizational principles of vesicle pools. However, only recently 38 has this method been successfully applied to small central synapses in native brain tissue, where neurons are retained in relevant circuits with defined cytoarchitecture.…”
Section: Labelling and Visualizing Functional Vesiclesmentioning
confidence: 99%
“…Interestingly, when preparations were rested after 15 min stimulation, the cisternae disappeared and SVs reappeared, suggesting the SVs could have derived from the cisternae [1]. Since this initial seminal study, a considerable number of studies have demonstrated that ADBE also occurs in rat hippocampal [6,17] and cerebellar granule [18] neurons, lamprey reticulospinal synapses [5], mouse calyx of Held [19] and auditory inner hair cells [20], snake [21] and Caenorhabditis elegans motor terminals [22], and goldfish bipolar neurons [8].…”
Section: Adbe At Neuronal Synapsesmentioning
confidence: 99%